Mechanisms of aging-related proteinopathies in Caenorhabditis elegans - 김동규; 김태호; 이승재 (Experimental & molecular medicine, 2016)
Aging is the most important risk factor for human neurodegenerative diseases such as Alzheimer’s and Parkinson’s diseases. Pathologically, these diseases are characterized by the deposition of specific protein aggregates in neurons and glia, representing the impairment of neuronal proteostasis. However, the mechanism by which aging affects the proteostasis system and promotes protein aggregation remains largely unknown. The short lifespan and ample genetic resources of Caenorhabditis elegans (C. elegans) have made this species a favorite model organism for aging research, and the development of proteinopathy models in this organism has helped us to understand how aging processes affect protein aggregation and neurodegeneration. Here, we review the recent literature on proteinopathies in C. elegans models and discuss the insights we have gained into the mechanisms of how aging processes are integrated into the pathogenesis of various neurodegenerative diseases. KCI Citation Count: 10